Seismic Imaging and Seismicity Analysis in Beijing-Tianjin-Tangshan Region - Xiangwei Yu; Wenbo Zhang; Yun-tai Chen (International Journal of Geophysics)
In this study a new tomographic method is applied to over 43,400 high-quality absolute direct P arrival times and 200,660 relative P arrival times to determine detailed 3D crustal velocity structures as well as the absolute and relative hypocenter parameters of 2809 seismic events under the Beijing-Tianjin-Tangshan region. The inferred velocity model of the upper crust correlates well with the surface geological and topographic features in the BTT region. In the North China Basin, the depression and uplift areas are imaged as slow and fast velocities, respectively. After relocation, the double-difference tomography method provides a sharp picture of the seismicity in the BTT region, which is concentrated along with the major faults. A broad low-velocity anomaly exists in Tangshan and surrounding area from 20 km down to 30 km depth. Our results suggest that the top boundary of low-velocity anomalies is at about 25.4 km depth. The event relocations inverted from double-difference tomography are clusted tightly along the Tangshan-Dacheng Fault and form three clusters on the vertical slice. The maximum focal depth after relocation is about 25 km depth in the Tangshan area.